Can Survey Participation Alter Household Saving Behaviour?. (24th March 2017) - Crossley, Thomas F.; de Bresser, Jochem; Delaney, Liam; Winter, Joachim
Abstract : We document an effect of survey participation on household saving. Identification comes from random assignment to modules within a population‐representative Internet panel. The saving measure is based on linked administrative wealth data. Households that responded to a detailed questionnaire on needs in retirement reduced their non‐housing saving rate by 3.5 percentage points, on a base of 1.5%. The survey may have acted as a salience shock, possibly with respect to reduced housing costs in retirement. Our findings present an important challenge to survey designers. They also add to the evidence of limited attention in household financial decision making.